Implementation of Maqashid Syariah in Preparing Financial Reports for Sharia Financial Institutions: Study at BPRS Al Salaam Cileungsi - Wijandari, Ana (International Journal of Economics (IJEC), 2024)
The aim of this research is to analyze how maqashid sharia is implemented in preparing the financial reports of BPRS Al Salaam Cileungsi. The research method used was a descriptive qualitative approach, through field research by examining published sharia financial reports and conducting interviews with management. Objectives in preparing sharia financial reports at BPRS Al Salaamin accordance with maqashid sharia, namely to fulfill the goal comprehensively in providing useful information to stakeholders. The objectives of sharia financial reporting include three levels, namely primary (dharuriyat), secondary (tahsiniyah), and tertiary (hajiyat). The primary aspect is very useful in providing financial information, that all financial institution activities come from halal sources. Meanwhile, the secondary aspect is able to provide additional information regarding compliance with sharia principles, as a form of protection for property development through contracts that comply with sharia principles. In the aspect of fulfilling the tertiary level, it shows that there is an urgency in presenting the assets owned by BPRS Al Salaam in a transparent and accountable manner, as an effort to be accountable to humans and Allah SWT, so as to provide benefits to more people. Compliance with these three aspects of maqashid sharia is a manifestation of benefit in the management of BPRS Al Salaam.